Comment on â€œPregnancy Screening before Diagnostic Radiography in Emergency Department; an Educational Reviewâ€ - Bijwaard, Harmen; Wit, Fleur (Archives of Academic Emergency Medicine, 2019)
With great interest we have read the paper â€œPregnancy Screening before Diagnostic Radiography in Emergency Department; an Educational Reviewâ€ by A.I. Abushouk et al. (1). We agree with the authors that unnecessary fetal radiation exposure should be avoided and that pregnancy screening can be a means to accomplish this. However, in their paper the authors suggest in several instances that radiological imaging during pregnancy can lead to teratogenic effects. In the Abstract it is stated: â€œRadiation exposure during pregnancy may have serious teratogenic effects to the fetus. Therefore, checking the pregnancy status before imaging women of child bearing age can protect against these effects.â€, and in the Introduction: â€œTherefore, checking the pregnancy status before imaging women of child bearing age can protect against radiation teratogenic effects.â€